the gcf is 6 because both 12 and 18 can be divided by 6.
the gcf is 2 because you cannot have a higher number
All of the following ordered pairs satisfy the function rule y = -3x + 2 except _____.(1, -1) (4, -10) (-2, 8) (-3, 12)
Answers
(-3,12)Because you substitute the 12 in for y and -3 in for x. Then you do you order of operations and you get 12=11 which is false.
2/7×15 can the answer be simplify
Answers
2/7*15 divide/multiply from left to right... 2/7*15=30/7 then simplify... 4 2/7
i hope that helped...
The answer may be simplify into 4 2/7. You do this because the answer was 30/7 30÷7= 4 2/7
How can you use subtraction to complete an addition pattern?
Answers
if you have an equation like 3+x=6 then you use subtraction by subtracting 3 from 6 to get 3 thats how you get the value of x (x=3) then you can go back and plug it in 3+3=6
Hope this helps!! :D
Hello! I Am going to show you an example. 3+3 = 6. 6-3 = 3 If You Need To Know What is A Number Just Count The Smaller Number And Count Until You Get To The Bigger Number. Example:7- 14 Count 7 until you get 14 lets count. 8,9,10,11,12,13,14 so that is 7 and to double check 14 - 7 is 7! Thats All!! :D
Hoped I Helped! Please Put Me As Best Answer
How can I solve this system of linear equation by substitution 3x+y=11 and -2x+y=1
Answers
We can answer this question by solving each equation for one variable, and then substituting.
3x + y = 11 Given y = -3x + 11 Subtract 3x from both sides
This equation is now solved for y. Now, let's do the other equation. Make sure to solve it for the same variable.
-2x + y = 1 Given y = 2x + 1 Add 2x to both sides
Now, let's set both equations equal to each other, since they both equal y.
2x + 1 = -3x + 11 Set both equations equal to each other 1 = -5x + 11 Subtract 2x from both sides -10 = -5x Subtract 11 from both sides 2 = x Divide both sides by -5
Now, let's substitute x in for one of the equations we found earlier, so that we can find y.
y = 2x + 1 Given y = (2)(2) + 1 Substitute the x-value, 2 y = 4 + 1 Multiply y = 5 Add
So, x = 2 and y = 5.
Hope this helps!
First will make Equation take on the form of y = mx + b. I've cchosen the second Equation:
y = 2x + 1
Now substitute this equation in for y into the other equation and solve: